Microseismic monitoring of hydraulic fracturing – data interpretation methodology with an example from Pomerania - Antoszkiewicz, Michał; Kmieć, Mateusz; Szewczuk, Paweł; Jankowski, Robert; Szkodo, Marek (International Conference “Environmental Engineering”, 2017)
Microseismic monitoring is a method for localizing fractures induced by hydraulic fracturing in search for shale gas. The aim of this paper is to conduct the data interpretation of the microseismic monitoring based on the results from Pomerania region of Poland. The data has been collected from an array of geophones deployed on the surface. Ground vibrations have been recorded and analyzed for fracture location, magnitude and breakage mechanism. A velocity model of underlying formations has been used for successful microseismic monitoring. The model has been further tuned with signal from perforation shots of known location. Imaging of events has been done using software MicSeis, which utilizes diffraction stacking of waveforms from multiple stations to image microseismic events with low signal tonoise ratio. The imaging of microseismic events in MicSeis uses a grid search over all possible origin times and locations in the selected rock volume. The seismic moment tensors are automatically determined from the amplitudes from the grid search procedure and are used to model polarities of events which then enhance constructive interference. Function characterizing a maximum stack per time sample have been calculated over whole volume and analyzed using the STA/LTA algorithm. Once the event has been detected in time, location has been determined through analysis of the 3D spatial image function. The procedure has been used to detect five events during hydraulic fracturing in Pomerania.
Keywords: microseismic monitoring; hydraulic fracturing; surface array